2021
DOI: 10.3390/agronomy11122468
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Soil-Borne Communities of Arbuscular Mycorrhizal Fungi during Natural Regrowth of Abandoned Cattle Pastures Are Indicative of Ecosystem Restoration

Abstract: Natural restoration of ecosystems includes the restoration of plant-microbial associations; however, few studies had documented those changes in tropical ecosystems. With the aim to contribute to understand soil microbial changes in a natural regrowth succession of degraded pastures that were left for natural restoration, we studied changes in arbuscular mycorrhizal (AM) fungal communities. Arbuscular mycorrhizal fungi (AMF) establish a mutualistic symbiosis with plants, improving plant nutrition. Amplificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
(99 reference statements)
0
2
0
Order By: Relevance
“…The pH and soil penetrations were typically altered by the cattle pasture use history of those forests [64]. Rodríguez-León et al [22] reported that soil pH decreases and organic carbon and nutrients such as Ca and Mg increase along the successional trajectory, favoring the establishment of arbuscular mycorrhizal fungal communities that are strongly associated with less-disturbed ecosystems. Likewise, the physical and biological quality of the soil is favored by natural regeneration, which will have a direct impact on the increase of species richness and composition of the plant community [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pH and soil penetrations were typically altered by the cattle pasture use history of those forests [64]. Rodríguez-León et al [22] reported that soil pH decreases and organic carbon and nutrients such as Ca and Mg increase along the successional trajectory, favoring the establishment of arbuscular mycorrhizal fungal communities that are strongly associated with less-disturbed ecosystems. Likewise, the physical and biological quality of the soil is favored by natural regeneration, which will have a direct impact on the increase of species richness and composition of the plant community [23].…”
Section: Discussionmentioning
confidence: 99%
“…Another determining factor in the regeneration pattern of vegetation cover is soil. The evidence suggests broad variation in the physical, chemical and biological conditions of the soil during secondary succession [22,23]. The wide heterogeneity of soils and their response to changes in cover generates a multifactorial scenario that may govern recovery trends for vegetation cover during natural regeneration.…”
Section: Introductionmentioning
confidence: 99%